1998
DOI: 10.1006/spmi.1997.0532
|View full text |Cite
|
Sign up to set email alerts
|

Thermopower of single-channel disordered and chaotic conductors

Abstract: We show (analytically and by numerical simulation) that the zerotemperature limit of the distribution of the thermopower S of a onedimensional disordered wire in the localized regime is a Lorentzian, with a disorder-independent width of 4π 3 k 2 B T /3e∆ (where T is the temperature and ∆ the mean level spacing). Upon raising the temperature the distribution crosses over to an exponential form ∝ exp (−2|S|eT /∆). We also consider the case of a chaotic quantum dot with two single-channel ballistic point contacts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 8 publications
5
56
0
Order By: Relevance
“…The most immediate effect of this failure is that the thermopower coefficient, which gives the voltage induced by a temperature gradient when no electrical current flows, becomes random in sign and is enhanced by (E F /E c )g −1 , where g ≡ G/G 0 is the dimensionless conductance and G 0 = e 2 /h. This enhancement can be many orders of magnitude, has been discussed in a number of previous works 8,9,10,11,12 , and has been measured in at least one experiment on quantum dots 13 .…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…The most immediate effect of this failure is that the thermopower coefficient, which gives the voltage induced by a temperature gradient when no electrical current flows, becomes random in sign and is enhanced by (E F /E c )g −1 , where g ≡ G/G 0 is the dimensionless conductance and G 0 = e 2 /h. This enhancement can be many orders of magnitude, has been discussed in a number of previous works 8,9,10,11,12 , and has been measured in at least one experiment on quantum dots 13 .…”
Section: Introductionmentioning
confidence: 68%
“…8,9 for the case of a disordered wire and in Ref. 11 for the case of a chaotic quantum dot. The thermopower Q = −B/G is the coefficient of the voltage induced by a temperature difference when no electrical current flows, I e = 0.…”
Section: Thermopowermentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, this symmetry may be violated when electron-phonon and electron-electron interactions are taken into account. While the Seebeck coefficient has always been found to be an even function of the magnetic field in two-terminal purely metallic mesoscopic systems [20], Andreev interferometer experiments [21] and recent theoretical studies [22,23] have shown that systems in contact with a superconductor or with a heat bath can exhibit nonsymmetric thermopowers. It is a challenging problem to find realistic setups with x significantly different from unity, while approaching the Carnot efficiency.…”
Section: Reduces To Eq (5) While Thermodynamics Does Not Impose Anymentioning
confidence: 99%
“…The charging effects are taken into account 2,27 by the function F (τ 1 ,τ 2 ): C being the capacitance of the cavity,…”
Section: Introductionmentioning
confidence: 99%